Advancements in Laparoscopic Partial Nephrectomy: Expanding the Feasibility of Nephron-Sparing. (9th May 2012) - Pietzak, Eugene J.; Guzzo, Thomas J.
Abstract : Partial nephrectomy (PN) offers equivalent oncologic outcomes to radical nephrectomy (RN) but has greater preservation of renal function and less risk of chronic kidney disease and cardiovascular disease. Laparoscopic PN remains underutilized likely because it is a technically challenging operation with higher rates of perioperative complications compared to open PN and laparoscopic RN. A review of the latest PN literature demonstrates that recent advancements in laparoscopic approaches, imaging modalities, ischemic mitigating strategies, renorrhaphy techniques, and hemostatic agents will likely allow greater utilization of LPN and expand its usage to increasingly more complex tumors.